2001
DOI: 10.1021/op000135p
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Reactor Technology for Ketal Formation:  An Improved Synthesis of Solketal

Abstract: The development of a fully continuous process for the synthesis of solketal (4-hydroxymethyl-2,2-dimethyl-1,3-dioxolane) is described. The use of a heterogeneous catalyst, recycle of unreacted starting material, elimination of the need for an entraining solvent, and purification of the product in situ all afford improvements over existing processes. Data generated in model reactions is used to prove the applicability of the process to a counter-current distillation reactor design, and to compute the operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 4 publications
2
39
0
2
Order By: Relevance
“…Synthesis of solketal Solketal has been prepared using conventional mineral acids, 181 and different homogeneous catalysts such as Ir complexes 182 or metal triflates. 183 Also a variety of heterogeneous catalysts have been used for this transformation.…”
Section: Glycerol Acetalsmentioning
confidence: 99%
“…Synthesis of solketal Solketal has been prepared using conventional mineral acids, 181 and different homogeneous catalysts such as Ir complexes 182 or metal triflates. 183 Also a variety of heterogeneous catalysts have been used for this transformation.…”
Section: Glycerol Acetalsmentioning
confidence: 99%
“…Clarkson et al used a multi-tray reactive distillation column with deep reaction stages containing catalyst (Amberlyst DPT-1) in suspension for the synthesis of solketal [52], as illustrated in Scheme 3. In their process, glycerol was preheated at 90°C before feeding into the reaction column.…”
Section: Development Of Continuous Processesmentioning
confidence: 99%
“…Approaches to completion of this reaction using homogeneous catalysis have been made, such as employing p-toluenesulphonic, sulphuric or hydrochloric acids [17,[25][26][27]. Efforts using solid catalysts appear to be the most followed trend, including the use of oxides of Group IV of the periodic table [28], zeolites [29,30], clays [29], heteropolyacids immobilized in silica [31], sulphonic acidfunctionalized mesostructured silicas [32,33], promoted zirconia [34], various sulphonated carbon silica mesocomposite materials [35], Sn-based salts, mesoporous substituted silicates [33]. With respect to the utilisation of solid catalysts, special mention must be made to the use of commercially available ion exchange resins.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the utilisation of solid catalysts, special mention must be made to the use of commercially available ion exchange resins. Table 1 compiles a brief review of the references found using such catalysts together with the conditions and operation modes used in each work to shift the equilibrium existing in this reaction towards the products [29,30,[36][37][38][39]. Selectivity of these catalysts towards the five-membered ring isomer of solketal has been reported to be practically 100% for the vast majority of the aforementioned acid catalysts.…”
Section: Introductionmentioning
confidence: 99%